2016
DOI: 10.1103/physrevlett.117.237601
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Strong Topological Insulator Phase in ZrTe5

Abstract: The complex electronic properties of ZrTe5 have recently stimulated in-depth investigations that assigned this material to either a topological insulator or a 3D Dirac semimetal phase. Here we report a comprehensive experimental and theoretical study of both electronic and structural properties of ZrTe5, revealing that the bulk material is a strong topological insulator (STI). By means of angle-resolved photoelectron spectroscopy, we identify at the top of the valence band both a surface and a bulk state. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
131
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(161 citation statements)
references
References 38 publications
13
131
3
Order By: Relevance
“…In the presence of the pressure, the Dirac cone is shifted away from the Fermi level and/or opens a finite energy gap. Recent works revealed that the Dirac semimetal state in ZrTe 5 is highly sensitive to the the lattice constants and manifests only at the boundary between the WTI and the STI phases [26,30]. In fact, our results show that it would not be completely destroyed until the pressure up to 2.5 GPa.…”
Section: Pacs Numbersmentioning
confidence: 57%
See 1 more Smart Citation
“…In the presence of the pressure, the Dirac cone is shifted away from the Fermi level and/or opens a finite energy gap. Recent works revealed that the Dirac semimetal state in ZrTe 5 is highly sensitive to the the lattice constants and manifests only at the boundary between the WTI and the STI phases [26,30]. In fact, our results show that it would not be completely destroyed until the pressure up to 2.5 GPa.…”
Section: Pacs Numbersmentioning
confidence: 57%
“…In addition, magnetoinfrared spectroscopy results, such as the linear energy dependence of optical conductivity and Landau level splitting, also support this scenario [24,25]. Very recently, Manzoni et al find out that the 3D Dirac semimetal phase manifests at the boundary between the weak and strong TI phases [26].Applying pressure is known to be a powerful approach to tune the electronic states and lattice structures without introducing disorder or impurity, which has been widely employed in topological materials. Recently, a pressure-induced semimetal to superconductor transition was observed in ZrTe 5 at 6.2 GPa [27].…”
mentioning
confidence: 90%
“…The resistivity peaks at 140 K, which is known as the resistivity anomaly 9-12 . Currently the most interesting question regarding ZrTe 5 is whether it is a 3D Dirac semimetal 16,18,19 , a 3D weak TI 21,22 , or a 3D strong TI 15 . The most essential evidence to distinguish these scenarios is to determine whether it has a gapless Dirac cone near Γ, or a gapped state, and to determine the existence of a TSS.…”
Section: (B-d)(blue Crosses)mentioning
confidence: 99%
“…Hall effect data shows electron-like carriers at low temperature [16], implying some of these additional bands must be populated and Dirac-like or massive Dirac-like features should be present. Note that these features are extremely sensitive to cell volume and strain [17], which may explain the conflicting experimental reports on the electronic properties and topological signatures in ZrTe 5 [4][5][6][7][8][9][10][11][12][13][14].…”
mentioning
confidence: 97%
“…In this study we focus on ZrTe 5 , a material whose topological nature is hotly debated; it has been predicted and verified as a Dirac semimetal [4][5][6][7][8], a topological insulator [9][10][11][12] and a trivial semiconductor [13,14]. In addition to its potential topological nature, there is also an unusual anomaly in the temperature dependence of the resistivity that has been conjectured to originate from a Lifshitz transition [15,16].…”
mentioning
confidence: 99%